2020
DOI: 10.1186/s12199-020-00869-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle behaviors and home and school environment in association with sick building syndrome among elementary school children: a cross-sectional study

Abstract: Background Sick building syndrome (SBS) refers to the combination of symptoms experienced by occupants of specific building characteristics. This study investigated the associations of children’s lifestyle behaviors, allergies, home, and school environment with SBS symptoms. Methods A total of 4408 elementary school children living in Sapporo City, Japan participated in this study. SBS was determined on parental answers to MM080 standardized school questionnaires on sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…A higher CO 2 concentration was significantly associated with a higher percentage of perceived stuffy odour and skin SBS symptoms in Chinese homes [28]. A study in Japan depicted that allergies and lifestyle behaviors were associated with increased SBS in children, including skipping breakfast, displaying faddiness, constipation, insufficient sleep, not feeling refreshed after sleep, and the lack of deep sleep [29].…”
Section: Of 22mentioning
confidence: 97%
“…A higher CO 2 concentration was significantly associated with a higher percentage of perceived stuffy odour and skin SBS symptoms in Chinese homes [28]. A study in Japan depicted that allergies and lifestyle behaviors were associated with increased SBS in children, including skipping breakfast, displaying faddiness, constipation, insufficient sleep, not feeling refreshed after sleep, and the lack of deep sleep [29].…”
Section: Of 22mentioning
confidence: 97%
“…For example, reducing the concentration of sum of volatile organic compounds (ΣVOCs) in living environments and the odor of specific chemicals can reduce the occurrence of building related symptoms (BRSs) [3,4]. In epidemiological studies, lifestyle changes such as frequent ventilation and cleaning were shown to reduce the occurrence of BRSs, asthma, and other allergic symptoms [5][6][7][8][9]. Very recently, improving the indoor-air environment through ventilation has proven effective against COVID19 infection [10,11].…”
Section: Introductionmentioning
confidence: 99%